Uji Aktivitas Sitotoksik Ekstrak Kulit Batang Tumbuhan Akar Kaik-Kaik (Uncaria Cordata) (Lour.) Meer Dengan Metode Brine Shrimp Lethality Test (BSLT) - Rahmawati, Noveri; Nurbaiti (As-Shiha: Jurnal Kesehatan, 2022)
In this study, a cytotoxic test of the root bark extract of kaik-kaik (Uncaria cordata)(Lour.)Merr was carried out using the Brine Shrimp Lethality Test (BSLT) method. The root bark extract of kaik-kaik (Uncaria cordata) (Lour.) Merr was obtained by maceration using n-hexane, ethyl acetate, and ethanol as solvents. The effect of each extract was identified on the percentage of mortality of Artemia salina Leach larvae and a probit analysis was calculated. The results showed that the three extracts provided cytotoxic activity with active categories with LC50 respectively, namely, 45.28 ug / ml, 55.08 ug / ml, 47.09 ug / ml which could be used as candidates for anti-cancer drugs